The effect of the concentration and oxidation state of Sn on the structural and electrical properties of indium tin oxide nanowires - Park, Kyung-Soo; Choi, Young-Jin; Kang, Jin-Gu; Sung, Yun-Mo; Park, Jae-Gwan (IOP PUBLISHING LTD, 2011)
High quality single-crystalline indium tin oxide (ITO) nanowires with controlled Sn contents of up to 32.5 at.% were successfully synthesized via a thermal metal co-evaporation method, based on a vapor-liquid-solid growth mode, at a substrate temperature of as low as 540 degrees C. The high solubility of Sn in the nanowires was explained with the existence of Sn2+ ions along with Sn4+ ions: the coexistence of Sn2+ and Sn4+ ions facilitated their high substitutional incorporation into the In2O3 lattice by relaxing structural and electrical disturbances due to the differences in ionic radii and electrical charges between Sn and In3+ ions. It was revealed that, while the lattice parameter of the ITO nanowires had a minimum value at a Sn content of 6.3 at.%, the electrical resistivity had a minimum value of about 10(-3) Omega cm at a Sn content of 14 at.%. These structural and electrical behaviors were explained by variation in the relative and total amounts of the two species, Sn2+ and Sn4+.
Keywords: THIN-FILMS; X-RAY; LOW-TEMPERATURE; SOLAR-CELL; ITO; DEPOSITION; GROWTH